Regulated cell death and DAMPs as biomarkers and therapeutic targets in normothermic perfusion of transplant organs. Part 1: their emergence from injuries to the donor organ - Land, Walter G.; Linkermann, Andreas (Frontiers in Transplantation, 2025)
This Part 1 of a bipartite review commences with a succinct exposition of innate alloimmunity in light of the danger/injury hypothesis in Immunology. The model posits that an alloimmune response, along with the presentation of alloantigens, is driven by DAMPs released from various forms of regulated cell death (RCD) induced by any severe injury to the donor or the donor organ, respectively. To provide a strong foundation for this review, which examines RCD and DAMPs as biomarkers and therapeutic targets in normothermic regional perfusion (NRP) and normothermic machine perfusion (NMP) to improve outcomes in organ transplantation, key insights are presented on the nature, classification, and functions of DAMPs, as well as the signaling mechanisms of RCD pathways, including ferroptosis, necroptosis, pyroptosis, and NETosis. Subsequently, a comprehensive discussion is provided on major periods of injuries to the donor or donor organs that are associated with the induction of RCD and DAMPs and precede the onset of the innate alloimmune response in recipients. These periods of injury to donor organs include conditions associated with donation after brain death (DBD) and donation after circulatory death (DCD). Particular emphasis in this discussion is placed on the different origins of RCD-associated DAMPs in DBD and DCD and the different routes they use within the circulatory system to reach potential allografts. The review ends by addressing another particularly critical period of injury to donor organs: their postischemic reperfusion following implantation into the recipient—a decisive factor in determining transplantation outcome. Here, the discussion focuses on mechanisms of ischemia-induced oxidative injury that causes RCD and generates DAMPs, which initiate a robust innate alloimmune response.